Influencia de la edad del cambium, tasa de crecimiento y nivel de precipitación sobre la densidad básica de la teca en Costa Rica - Moya Roque, Róger (Instituto de Ecología, A.C., 2016)
Teak (Tectona grandis) is an important species for commercial reforestation in Costa Rica and it is sold as “baby teak” in the international market due to the fact that it comes from plantations not older than 10 years. Furthermore, teak has shown excellent growth in places where the rainfall exceeds 3500 mm/year and where there is not a well defined dry season, which is different to the natural conditions where it grows naturally in Asia. The objective of this study was to determine the change in specific gravity (Ow/Gv) in the radial direction, from the pith to the bark, as well as the influence of cambium age, growth rate and precipitation in trees growing at the Caribbean side of the Costa Rica. In order to do this, cross sections were cut at breast height (DBH) and growth rate, in terms of growth ring thickness, and specific gravity per ring, were recorded. Results showed that specific gravity increases from pith to bark and that it is affected by cambium age and growth rate, the former being the one that most influences this variable. On the other hand, precipitation rate, did not affect significatively the specific gravity of wood in trees younger than 9 years old. Other important result was that in intensive managed plantation the relationship between basic density and cambium age or growth rate decrese.